Impact of allopurinol on risk of myocardial infarction. Issue 5 (6th January 2014) - Grimaldi-Bensouda, L; Alpérovitch, A; Aubrun, E; Danchin, N; Rossignol, M; Abenhaim, L; Richette, P; ,
Abstract : Background: Gout therapy includes xanthine oxidase inhibitors (XOI) and colchicine, which have both been associated with decreased cardiovascular risk. However, their effects on major cardiac events, such as myocardial infarction (MI), need to be investigated further. Objectives: To investigate whether XOIs and colchicine are associated with decreased risk of MI. Methods: This case-control study compared patients with first-ever MI and matched controls. Cases were recruited from the Pharmacoepidemiological General Research on MI registry. Controls were selected from a referent population (n=8444) from general practice settings. Results: The study sample consisted of 2277 MI patients and 4849 matched controls. Use of allopurinol was reported by 3.1% of cases and 3.8 of controls, and 1.1% of cases and controls used colchicine. The adjusted OR (95% CI) for MI with allopurinol use was 0.80 (0.59 to 1.09). When using less stringent matching criteria that allowed for inclusion of 2593 cases and 5185 controls, the adjusted OR was 0.73 (0.54 to 0.99). Similar results were found on analysis by sex and hypertension status. Colchicine used was not associated with a decreased risk of MI (aOR=1.17 (0.70 to 1.93)). Conclusions: Allopurinol may be associated with a reduced risk of MI. No decreased risk of MI was found in colchicine users. Besides its urate-lowering property, allopurinol might have a cardioprotective effect.